LOW TOTAL CHOLESTEROL SERUM LEVELS AS A POOR OUTCOME PREDICTOR FOR INTRA-CEREBRAL HEMORRHAGE STROKE - Ariswanda, I Gusti Agung Gede; Adnyana, I Made Oka; Widyadharma, I Putu Eka; Nuartha, A A B N; Laksmidwei, A A A Putri; Arimbawa, I Komang (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Stroke is affected by several factors, age, infection during treatment, obesity, and total cholesterol (TC) levels. Objective: The study aimed to prove low TC serum levels as an unfortunate outcome predictor for intracerebral hemorrhage stroke. Methods: This study is a prospective cohort design. The research did in the Stroke Unit of Sanglah Hospital, Denpasar, from July 1st, 2018 to January 31th, 2019. The study involved patients with hemorrhage strokes with low TC serum levels and aged 40-95 years. Depending on variable divided into two groups with low TC serum levels (<180 mg/dL) and normal TC serum levels (>180mg/dL). Independent variable is The National Institutes of Health Stroke Scale (NIHSS) as an outcome. The processing of data analysis using Mac for SPSS version 23. Result: This study used 70 subjects. The age characteristics of the study subjects with a median value of 62 years in for low TC levels, and 57 years for normal TC levels, dominant in male (60% ), working (71.5%), not obese (58.6%), stroke-related infections (51.4%), and mean arterial blood pressure (MABP) £130mmHg (90%). Subjects with low TC had a risk of 64 times experiencing adverse outcomes (RR = 64: CI 95% = 14.06-291.32: p <0.001). Multivariate analysis showed a low TC serum level as an independent variable.Conclusion: Low TC serum levels as an independent predictor having a poor outcome in intracerebral hemorrhage stroke